2020
DOI: 10.1021/acs.est.0c02142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N-Nitrosamines and Nitrogenous Heterocyclic Byproducts during Chloramination of Aromatic Secondary Amine Precursors

Abstract: With diminishing pristine water, wastewater-affected waters that contain complex anthropogenic compounds are becoming important sources of drinking water and the compounds will inevitably react with disinfectants to form disinfection byproducts (DBPs). Secondary amines such as diphenylamine (DPA) analogues are considered as potential precursors of N-nitrosamines. In this study, an in situ 14N/15N-labeling and screening workflow was used to systematically investigate the formation of nitrogenous DBPs (N-DBPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Nontarget analysis has become a practicable and reliable approach for screening and identification of environmental pollutants, which can alleviate the dilemma in lack of reference standards. , By means of state-of-the-art analytical technologies in terms of chromatography and high-resolution mass spectrometry (HRMS), many nontarget analysis methods for environmental pollutants have been developed in recent years. The advanced technologies employed in nontarget analysis mainly include liquid chromatography-quadrupole-Orbitrap HRMS (LC-Q-Orbitrap-HRMS), gas chromatography-Q-Orbitrap-HRMS (GC-Q-Orbitrap-HRMS), , LC-quadrupole time-of-flight MS (LC-QTOF-MS), GC-QTOF-MS, , and Fourier transform ion cyclotron resonance MS (FT-ICR-MS). , In many studies concerning the identification of PFASs, nontarget analysis has also been used, and >1000 previously unrecognized PFASs have been continuously found in various matrices, such as commercial products, , environmental matrices, and biological samples. , These nontarget analysis methods mainly utilized LC-Q-Orbitrap-HRMS , and LC-QTOF-MS, ,, with data acquisition modes in full scan, , data-dependent acquisition (DDA) and data-independent acquisition (DIA). ,, Characteristic fragment ions such as C 2 F 5 – , C 3 F 5 – , FSO 3 – , HSO 4 – , PO 3 – , and NSO 2 – were used for tracing quasi-molecular ions, , thus identifying PFASs. Moreover, carbon and sulfur isotopologue distributions are also useful features for the screening and identification of PFASs as some previous studies have applied isotopic patterns to facilitating nontarget identification of PFAS pollutants. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Nontarget analysis has become a practicable and reliable approach for screening and identification of environmental pollutants, which can alleviate the dilemma in lack of reference standards. , By means of state-of-the-art analytical technologies in terms of chromatography and high-resolution mass spectrometry (HRMS), many nontarget analysis methods for environmental pollutants have been developed in recent years. The advanced technologies employed in nontarget analysis mainly include liquid chromatography-quadrupole-Orbitrap HRMS (LC-Q-Orbitrap-HRMS), gas chromatography-Q-Orbitrap-HRMS (GC-Q-Orbitrap-HRMS), , LC-quadrupole time-of-flight MS (LC-QTOF-MS), GC-QTOF-MS, , and Fourier transform ion cyclotron resonance MS (FT-ICR-MS). , In many studies concerning the identification of PFASs, nontarget analysis has also been used, and >1000 previously unrecognized PFASs have been continuously found in various matrices, such as commercial products, , environmental matrices, and biological samples. , These nontarget analysis methods mainly utilized LC-Q-Orbitrap-HRMS , and LC-QTOF-MS, ,, with data acquisition modes in full scan, , data-dependent acquisition (DDA) and data-independent acquisition (DIA). ,, Characteristic fragment ions such as C 2 F 5 – , C 3 F 5 – , FSO 3 – , HSO 4 – , PO 3 – , and NSO 2 – were used for tracing quasi-molecular ions, , thus identifying PFASs. Moreover, carbon and sulfur isotopologue distributions are also useful features for the screening and identification of PFASs as some previous studies have applied isotopic patterns to facilitating nontarget identification of PFAS pollutants. ,, …”
Section: Introductionmentioning
confidence: 99%
“…By virtue of recent advances in chromatography and high-resolution mass spectrometry (HRMS), numerous nontarget and suspect screening analysis methods for environmental pollutants have been rapidly developed [18][19][20][21][22] . The cutting-edge analytical techniques applied in nontarget and suspect screening analyses mainly include liquid chromatography coupled with quadrupole-Orbitrap HRMS (LC-Q-Orbitrap-HRMS) [23][24][25][26][27] , gas chromatography coupled with Q-Orbitrap-HRMS (GC-Q-Orbitrap-HRMS) 28,29 , LC coupled with quadrupole time-of-flight MS (LC-QTOF-MS) [30][31][32] , GC-QTOF-MS 33,34 , Fourier transform ion cyclotron resonance HRMS (FT-ICR-HRMS) 35,36 , etc. Nontarget and suspect analyses have also been applied in the screening and identification of PFASs, and more than 1000 previously unrecognized PFASs have been identified in various matrices recently 37 , e.g., commercial products 1,38,39 , environmental matrices [40][41][42] and biological samples 2,43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…Disinfection processes, used for the public water system and aimed at inactivating viable pathogenic microorganisms and protecting against the occurrence of water-borne diseases, were considered as a significant public health triumph in the beginning of the 20th century [ 1 , 2 , 3 ]. However, it has been well demonstrated that several disinfection byproducts (DBPs) are unavoidably formed from the reaction between disinfectants and naturally organic matter, organic contaminants, or halides during water purification treatment [ 4 , 5 ]. Since the first group of DBPs, i.e., trihalomethanes (THMs), was found in 1974 [ 6 ], more than 800 DBPs belonging to various classes have been gradually determined both in real disinfection plants and in controlled laboratory tests [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%